Histories of Human Rights in the Nordic Countries. Issue 3 (3rd July 2018) - Vik, Hanne Hagtvedt; Jensen, Steven LB; Lindkvist, Linde; Strang, Johan
ABSTRACT: Do the Nordics warrant the label 'global good Samaritans' in human rights promotion? Is the Nordic welfare state a close to perfect realisation of human rights norms? Alternatively, do Nordic international and domestic human rights policies constitute a peculiar 'Nordic human rights paradox' where norms are supported internationally while not being implemented at home? In what is the first collection of articles on Nordic human rights history, we take issue with previous scholarship, finding it often to be unsubstantiated and lacking a basis in historical contexts and relevant source materials. This also includes the stream of historical studies in the past decade, where, until recently, the Nordic countries have represented something of a blind spot. However, the lack of prior interest in the region means there are several promising avenues for historical investigations of both the Nordic countries in human rights history and the role of human rights in the history of the region.